Effects of turbulator with round hole on the thermo-hydraulic performance of nanofluids in a triangle tube. (January 2020) - Qi, Cong; Fan, Fan; Pan, Yuhang; Liu, Maoni; Yan, Yuying
Graphical abstract: The experimental system: (a) Schematic diagram. (b) Physical diagram. Highlights: Effects of round hole diameter on the flow and heat transfer are studied. Effects of pitch-row on the flow and heat transfer are studied. Thermal and exergy efficiency for thermo-hydraulic performances are studied. Abstract: For investigating the thermal and hydraulic characteristics of water-based SiO2 nanofluids in a triangular tube with different turbulators, an experimental system has been designed and verified in this paper. The effects of different round hole diameters ( d  = 3 mm, 4 mm, 5 mm) and round hole pitch-rows ( l  = 5 cm, 10 cm, 15 cm) of perforated turbulators on the thermo-hydraulic characteristics are researched. Meanwhile, the influences of Reynolds numbers ( Re  = 400–8000) and nanoparticles mass fractions (D-I water, ω  = 0.1%, 0.3%, 0.5%) are also studied. These experimental results show that, under the same circumstance, the nanofluids in the triangular tube with ω  = 0.5% have the largest positive influence on the heat transfer enhancement ratio which is up to 16.73%. For a comprehensive study of the flow and heat transfer, thermal efficiency (comprehensive performance index) and exergy efficiency are adopted. It can be found that the larger the diameter and the smaller the pitch-row of the holes is, the greater the comprehensive evaluation index can be. In addition, all working conditions exhibit the superior exergy efficiency. The highest exergy efficiency can be got when Re  = 6000 and ω  = 0.5%.